Because Philosophy is for Children: Diseño e intervención de una propuesta innovadora para medir el impacto de la Filosofía para Niños en un colegio rural (Journal of Parents and Teachers, 2023)
Philosophy is usually linked to higher educational levels and sometimes its usefulness in the school curriculum is even debated. In my Final Degree Project, I present an innovative proposal that demonstrates the importance of bringing philosophy to the classroom, even from an early age. This discipline cultivates deep reflection skills, essential in a society in constant change. This work seeks to measure the impact of applying this methodology in a rural classroom.
Keywords: rural school; philosophy for children; children's stories; critical thinking; multilevel classroom